Financial Performance of The Province of Riau Archipelago in The Context of The Degree of Independence, Degree of Dependence, and Fiscal Decentralization - Norman Syah Putra (Fakultas Pendidikan Ekonomi dan Bisnis, 2022)
Riau Archipelago is one of the provinces established in the regional autonomy era. The province is enforced to well manage its local own-resources in realizing regional autonomy. This study is aimed at analyzing the degrees of independence, dependence, and fiscal decentralization of the province. Through the ratio analysis, it is expected that this study can give some references to the Provincial Government taken as the subject of the study, i.e. related to decision making aimed at increasing its regional independence as well as decreasing the dependency towards the Central Government. This study uses the Report on Local Government Finances of the Province of Riau Archipelago for the financial year of 2014-2020 as the research data. This study uses quantitative descriptive analysis method based on the local government finance ratios including regional financial independence ratio, regional financial dependence ratio, and regional fiscal decentralization ratio. This study shows that from regional independence aspect, the financial performance of the province is in medium fiscal capacity (55.84%) with participative relational pattern. Based on the degree of regional dependence aspect, it is in very high category (64.17%) while due to regional fiscal decentralization degree, its regional financial performance is in good category with an average of 35.69%.